From the history of Petru Rareș fight for Transylvania - Niemczyk-Wiśniewska, Katarzyna (Balcanica Posnaniensia. Acta et studia, 2022)
The aim of the paper is to talk over the fight for Transylvania. The main person who was interested in conquering this territory was the ruler of Moldova Petru Rares. After battle of Mohacs, where the king of Hungary — Ludwik Jagiellon died — the war between Ferdinand Habsburg and Johannes Zapolya and Suleyman the Great began. And Transylvania was in the middle of this conflict. Petru Rares wanted to make use of this situation and conquer this territory.